2020
DOI: 10.1136/bmjopen-2019-031799
|View full text |Cite
|
Sign up to set email alerts
|

Association between cardiovascular risk factors and coronary artery disease assessed using CAD-RADS classification: a cross-sectional study in Romanian population

Abstract: ObjectivesThis study aimed to evaluate the association between cardiovascular risk factors and Coronary Artery Disease—Reporting and Data System (CAD-RADS) score in the Romanian population. CAD-RADS is a new, standardised method to assess coronary artery disease (CAD) using coronary CT angiography (CCTA).DesignA cross-sectional observational, patient-based study.SettingReferred imaging centre for CAD in Transylvania, Romania.ParticipantsWe retrospectively reviewed 674 patients who underwent CCTA between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…Therefore, MHR is expected to increase in patients with high CAD-RADS scores. Overall, the relationship between diabetes and CAD and CAD-RADS score is well-established (42). Moreover, there is a strong relationship between hyperglycemia and CAD, even in the prediabetic stage.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, MHR is expected to increase in patients with high CAD-RADS scores. Overall, the relationship between diabetes and CAD and CAD-RADS score is well-established (42). Moreover, there is a strong relationship between hyperglycemia and CAD, even in the prediabetic stage.…”
Section: Discussionmentioning
confidence: 90%
“…The association of age and male sex with cardiac death and major adverse cardiovascular events is well-known. In this regard, Popa et al found a significant independent relationship between the CAD-RADS score and age and male sex (42,43). In the current study, an independent relationship was also observed between the CAD-RADS score and age and male sex; the CAD-RADS score was higher in men than in women.…”
Section: Discussionmentioning
confidence: 98%
“…A higher mortality has been reported in male than female [ 31 ]. Male has always been a risk factor for cardiovascular diseases [ 32 ]. Besides sex-specific cancer, the prevalence in male and female is > 1 for all cancers, and the cancer-related burden is higher in male than female [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases represent a main cause of death worldwide, and among European countries, Romania has a high cardiovascular disease (CVD) prevalence and mortality burden [ 1 ]. Cardiomyopathies are a heterogeneous group of myocardial diseases associated with mechanical and/or electrical dysfunction, accompanied or not by hypertrophy or dilation, of acquired or congenital causes.…”
Section: Introductionmentioning
confidence: 99%